2014
DOI: 10.1016/j.jallcom.2013.08.140
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and crystal structure of K2NiF4-type novel Gd1+xCa1−xAlO4−xNx oxynitrides

Abstract: Novel gadolinium calcium aluminum oxynitrides, Gd 1+x Ca 1-x AlO 4-x N x , were prepared in x = 0.15-0.25 by the solid state reaction of a nitrogen-rich mixture with AlN as an aluminum source; the mixture was sintered twice at 1500C for 5 h under 0.5 MPa of nitrogen gas. Shift in the optical absorption edge was observed in their diffuse reflectance spectra from 4.4 eV for the oxide (x = 0) to 2.9 eV for the oxynitride at x = 0.2. The crystal structure of Gd 1.2 Ca 0.8 AlO 3.8 N 0.2 at x = 0.2 was refined usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The bonds between metals and anions determine crystal structures and affect physical properties, and recent advances in mixed-anion chemistry have been based on understanding and controlling the effects of anions [1][2][3]. LnO 1-x F x BiS 2 (Ln: La, Ce, Pr, Nd, or Yb) are superconducting mixed-anion layered compounds [4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The bonds between metals and anions determine crystal structures and affect physical properties, and recent advances in mixed-anion chemistry have been based on understanding and controlling the effects of anions [1][2][3]. LnO 1-x F x BiS 2 (Ln: La, Ce, Pr, Nd, or Yb) are superconducting mixed-anion layered compounds [4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, mixed anion compounds, whose properties can be tuned by incorporating different anions, have received considerable interest . Ln(O,F)BiS 2 (Ln: La, Ce, Pr, Nd, Yb) complexes constitute a class of layered mixed-anion superconductors with structures consisting of BiS 2 conductive planes and Ln(O,F) blocking slabs. , Of this class of complexes, Ce(O,F)BiS 2 has exhibited both superconductive and ferromagnetic-like properties. Magnetic ordering in La(O,F)BiS 2 , Pr(O,F)BiS 2 , and Nd(O,F)BiS 2 has not been reported thus far, suggesting that the magnetic ordering in Ce(O,F)BiS 2 can be attributed to the Ce(O,F) layers.…”
Section: Introductionmentioning
confidence: 99%
“…Oxynitride (AB­(O,N) 3 ) perovskite materials are another important class of perovskite materials that are obtained by substituting oxygen with nitrogen, and these materials are experimentally synthesized by ammonolysis of oxide perovskites . However, the distribution of nitrogen at the oxygen site is still under discussion. , …”
Section: Introductionmentioning
confidence: 99%
“…32 However, the distribution of nitrogen at the oxygen site is still under discussion. 33,34 It is observed that the greater ionic radius of a nitride ion (N 3− , 1.50 Å) 35 compared to that of oxide ion (O 2− , 1.4 Å) permits the possibility of numerous perovskite nitride compounds with multiple compositions such as ABO 2 N, ABON, and ABN 3. 32,33 However, only a few perovskite nitrides have been synthesized where cation A can be Ca, Sr, Ba, Eu, La, Pr, Nd, or Sm and cation B can be Ti, Zr, V, Mo, Nb, or Ta, such as in compounds BaTaO 2 N, CaTaO 2 N, SrBO 2 N, and SrTaO 2 N. 36 In addition, density functional theory has been used to predict compounds with Mo and W. 33 The photocatalytic activity of these theories has been implemented to report several hypothetical nitride compounds showing photocatalytic capability improved over that of the the already synthesized nitrides, for example, MgTaO 2 N, YTiO 2 N, and CdTaO 2 N. 36 The experimental realization of these hypothetical nitride compounds might be associated with the difficulty of perovskite materials in these compounds, or it might be related to the difficulty of synthesizing these compounds.…”
Section: Introductionmentioning
confidence: 99%